EDUKASI PERAN ORANG TUA DALAM PEMBENTUKKAN INNER CHILD MELALUI REGULASI EMOSI ANAK DI GEREJA BACB - Purnama, Jellia Puspa; Hermanto, Yanto Paulus (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2024)
The inner child is a part of someone's life that is formed from the time of conception until the age of 12. Therefore, parents play a crucial role in shaping the inner child. If someone has a wounded inner child, it will manifest unconsciously throughout adulthood, both in actions and feelings. One thing a parent can do is regulate their child's emotions. An educational class for parents held at the Bandung City Blessing City Square Church aims to raise awareness regarding the importance of understanding the inner child and emotional regulation in children. The research method used is descriptive qualitative, where the author conducted a literature study to present the material for this educational class. Doing this activity resulted in participants giving positive responses, indicating that the class provided knowledge and skills that can be directly applied. Participants also suggested that educational courses should be conducted regularly and counselling should be available for parents to enhance their parenting abilities further.